Determinants of Pastoralists' Nutrition Security in Itang Special District, Gambella, Ethiopia - Chayot Gatdet (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
The malnutrition is widespread challenge in the Itang special district of Gambella. The main aim of this study was to examine the determinants of pastoralists' nutrition security in Itang special district. It collected the primary data through households' interview schedule, key informants interview and body mass index and; the secondary data were collected by document analysis. Then, the descriptive statistics mainly frequency, percentage, mean, standard deviation, and binary logit model were used to analyse the data by using SPSS version 20. The field result revealed that about 65% and 35% of the rural households were nutrition secured and unsecured respectively in the district. Similarly, the binary logit model result indicated that the livestock size, dietary diversity status, educational status and income were statistically significant at 1% while; the market access and awareness were statistical significant at 5%.